Pengaruh Debt To Equity Ratio, Operating Profit Margin, dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Cut Anisya Al Winda; Aliamin Aliamin; Sulfitra Sulfitra (Jurnal Sains dan Ilmu Terapan, 2026)
This research aims to examine the impact of Debt to Equity Ratio (DER), Operating Profit Margin (OPM), and firm size on the value of food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2023 period. In this study, firm value is measured using Price to Book Value (PBV) as a proxy. A quantitative associative design was applied, utilizing panel data regression analysis and a purposive sampling technique that produced 10 eligible companies as research samples. The data were collected from the firms’ published annual financial statements. The findings indicate that, partially, DER and firm size do not significantly influence firm value, whereas OPM demonstrates a positive and statistically significant effect. These results suggest that profitability plays a more decisive role than capital structure or company scale in determining firm value within the food and beverage subsector. This study is expected to offer valuable insights for corporate managers, investors, and future researchers regarding key determinants of firm value in this industry segment.